Videoaprendizagem: uma metodologia ativa experimental para o ensino superior - MACIEL, Mayara Santos (Universidade Federal do Pará, 2020)
This work aims to present and analyze the process of idealization, elaboration, experimentation, selection and validation of a methodological proposal for higher education, a so - called Videoaprendizagem. It is a proposal of pedagogical practice with emphasis on innovative and creative disciplines of education, because it redesigns teaching and learning relations in the classroom, allowing structural conditions for a teaching and learning autônomo for students starting from the critical thinking about digital technologies, focusing on the processes of creating pocket videos. The theoretical construction of this work is supported by the considerations of Heidegger (1994) and Orozco-Gómez (2002, 1998) on the “Essence of the Technique” and “Rationality of Relevance”, in the precepts of Martín-Barbero (2000) and Moran (2013, 2007, 2002, 1995, 1994 ). (2018), Valente (2018), Althaus and Bagio (2017), Souza, Iglesias and Pazin-Filho (2014) and Miter et al. (2008) on active methodologies. We refer to Freire (2011) and Zatti (2007) to face the younger (2012) and Moreira and Masini (1982) in order to deal with a more important learning, besides Paulo Freire (1986). technical guidelines for making videos by Moletta (2009) and Alves et al. (1987). A qualitative research has as main script a participant examiner (YIN, 2016; MINAYO, 2009b; GIL, 2008). As support techniques use the research (BONIN, 2011) and a documentary research (SÁ-SILVA; ALMEIDA; GUINDANI, 2009). To collect data on research changes, we use the data game, a playful adaptation of the world made by us. The selection and validation of consumer products (Videoaprendizagem guide, website and Basic Pocket Videos Production Manual) was carried out from a panel of Specialists (PINHEIRO, FARIAS, LIMA, 2013, STRUCHINER, RICCIARDI, VETROMILLE, 1998). The results of the research were developed and incorporated into the generation of videos and results of its derivatives, as well as the proposal for the creation of workspaces and the learning of meaningful learning.